Antithesis as a structuraland semantic organization principle of a Kabardian-Circassian proverb - Dina M. Kumykova; Elina T. Kumykova (Cuchapsheva) (Кавказология, 2024)
The principle of contrastive pattern on the structural and semantic levels in the proverbial text arrangement, according to leading paremiologists, constitutes one of the most striking paremic markers. The implementation of this principle in Kabardian-Circassian proverbs is still insufficiently studied. Systematization of the inventory of stylistic devices through which opposition is realized in Kabardian-Circassian proverbs stamps one of the urgent tasks. The presented work brings us closer to the solution of the issue. The article is devoted to the investigation of one of the main stylistic figures of expressing contrast in a proverb - antithesis as a form of demonstratively highlighted opposition. The classification of the phenomena is proposed as based on the structural and functional characteristics of this stylistic figure. The most representative types of antitheses have been determined concerning Kabardino-Circassian paremias. The study reveals that contextual antonymic correlations along with linguistic antonyms productively participate in generating proverbial antithesis.  The antonymizing explicator of the lexical units, containing potential opportunities for their contrastive opposition proves to be the antithetical construction itself. The study of the structural and semantic features of Kabardino-Circassian proverbs convinces us of the universality of proverbial antithesis as  essential means of expressing contrast, as well as the specificity of the ways of its formation, which determines the prospects for its further study. The main empirical base for the study of Kabardian-Circassian proverbs and sayings based on contrast comprise the material selected from collections of proverbs of 1994 (compiled by A. Gukemukh, Z. Kardangushev) and 2016 (compiled by L. Gutova), using a continuous sampling methodology.